2023
DOI: 10.1093/pnasnexus/pgad077
|View full text |Cite
|
Sign up to set email alerts
|

Diversity beyond density: Experienced social mixing of urban streets

Abstract: Urban density, in the form of residents’ and visitors’ concentration, is long considered to foster diverse exchanges of interpersonal knowledge and skills, which are intrinsic to sustainable human settlements. However, with current urban studies primarily devoted to city and district-level analysis, we cannot unveil the elemental connection between urban density and diversity. Here we use an anonymized and privacy-enhanced mobile data set of 0.5 million opted-in users from three metropolitan areas in the U.S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The place where a person lives can have substantial impacts on health (Wilkinson and Pickett, 2006), economic opportunities (Chetty et al, 2014(Chetty et al, , 2016, infrastructure and services accessibility (Glaeser et al, 2001;Reid et al, 2016;Florida, 2017), and many other aspects, both at a city and national scale (Chetty et al, 2014;Shelton et al, 2015). Thus, measuring inequalities and segregation with timely and accurate data is of paramount importance, and alternative data sources and ubiquitous technologies are starting to play a central role in deeply analyzing factors and behaviors associated to inequalities such as environmental inequalities (Brazil, 2022;Dass et al, 2022), social mixing and income segregation (Shelton et al, 2015;Moro et al, 2021;Fan et al, 2023), and community resilience (Hong et al, 2021).…”
Section: Computational Methods Big Data and Inequalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The place where a person lives can have substantial impacts on health (Wilkinson and Pickett, 2006), economic opportunities (Chetty et al, 2014(Chetty et al, , 2016, infrastructure and services accessibility (Glaeser et al, 2001;Reid et al, 2016;Florida, 2017), and many other aspects, both at a city and national scale (Chetty et al, 2014;Shelton et al, 2015). Thus, measuring inequalities and segregation with timely and accurate data is of paramount importance, and alternative data sources and ubiquitous technologies are starting to play a central role in deeply analyzing factors and behaviors associated to inequalities such as environmental inequalities (Brazil, 2022;Dass et al, 2022), social mixing and income segregation (Shelton et al, 2015;Moro et al, 2021;Fan et al, 2023), and community resilience (Hong et al, 2021).…”
Section: Computational Methods Big Data and Inequalitiesmentioning
confidence: 99%
“…The authors discovered inequalities, where communities with higher infections and higher prevalence of black residents experienced greater infection exposure per visit. Fan et al ( 2023 ) employed mobile phone data of half a million people located in three different metropolitan areas in the US to study how people experienced social mixing in urban streets. The authors found that the density of people's street visits only explains the 26% of street-level diversity (e.g., social mixing), while the adjacent amenities, residential diversity, and income level explain the 44% of the designed diversity score.…”
Section: Socioeconomic Inequalities and Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction intensity, defined as the density of population and buildings, engenders a bustling, diverse urban milieu, thereby invigorating urban streets [38]. Diversity, encompassing cultural, commercial, social, and economic facets, enriches urban streets by offering a variety of activities and choices [39]. The functional nature signifies the primary purposes and characteristics of a street.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Mobility as the fabric of human societies has been studied for understanding the mechanism of movements [1][2][3][4][5][6][7], diffusive processes [8,9], and its association with socioeconomic attributes [10][11][12][13][14][15] at both individual and population levels. Taking advantage of rich data, several population-level mobility models were developed to describe travel patterns as a function of geographical factors, e.g., population distribution and travel distance.…”
Section: Introductionmentioning
confidence: 99%